ChemInform Abstract: Comprehensive System Integrating 3D and 2D Zeolite Structures with Recent New Types of Layered Geometries. Issue 23 (10th June 2014) - Roth, Wieslaw J.; Gil, Barbara; Marszalek, Bartosz
Abstract Review: 59 refs.